Analysis and Design of Breeding Management Information System in Poultry Farms - Alexius Hendra Gunawan; Verry Kuswanto; Junaedi (Komunitas Dosen Indonesia, 2024)
Breeding management is indispensable in business development in the field of poultry farming where companies are required to keep up with the development of the digitalization era. Companies must be able to take advantage of opportunities in advances in information technology in obtaining accurate, fast and reliable information so that management can make decisions. PT. Peternakan Ayam Manggis has been using manual methods in recording the results of production or the process of breeding chicken farms. in making records using office software, namely excel, so that errors often occur and are often not realtime in making records. Records generated by poultry production include depletion, quarantine, culling, feed and egg production. in processing data generated manually can make it difficult for management to make decisions. The purpose of this research is to design an application that can be used by companies to obtain information during the breeding process.The research method in developing this application uses waterfall and design role analysis with data collection and using UML modeling. This information system application produces information about Breeding management including depletion, quarantine, feed, egg production, movement of chickens from one cage to another, culling. this information system application uses a database and application blackbox testing is carried out so that the application runs as needed.